Peptides and Pseudopeptides as SIRT6 Deacetylation Inhibitors - Kokkonen, Piia (American Chemical Society, 2012)
[Image: see text] SIRT6 belongs to the family of histone deacetylases (class III), but it also has mono-ADP-ribosyltransferase activity. SIRT6 is a nuclear sirtuin that has been associated with aging, cellular protection, and sugar metabolism. Despite these important roles for SIRT6, thus far, there are only a few weak SIRT6 inhibitors available, and no structure–activity relationship (SAR) studies have been published. This is the first study concerning peptides and pseudopeptides as SIRT6 deacetylation inhibitors and the first SAR data concerning SIRT6. We also investigated the molecular interactions using a homology model. We report three compounds exhibiting 62–91% SIRT6 inhibition at 200 μM concentration. These compounds can serve as starting points for systematic SAR studies and SIRT6 inhibitor design.